O06.5 Development of a human urethral equivalent to study chlamydia trachomatis invasion. (8th July 2017) - Versteeg, Bart; Broek, Lenie Van Der; Bruisten, Sylvia; Mullender, Margriet; Vries, Henry De; Gibbs, Sue
Abstract : Introduction: Chlamydia trachomatis (Ct) genovars D-K cause non-invasive urogenital infections, which often remain asymptomatic. Little is known about the invasion of the epithelial layer and the subsequent effects of Ct on the epithelium in humans. The objective of this study was to develop a human urethral 3D in vitro equivalent to gain a better insight into the invasiveness of Ct in host tissue. Methods: Human urethral equivalents were constructed by seeding primary urethral keratinocytes and fibroblasts on top of and into a collagen matrix. Urethral cells were isolated from urethral clinical specimens of transgender patients undergoing gender surgery at VUMC. Urethral equivalents were incubated with a Ct genovar D strain, by placing a Ct impregnated nylon gauze on top of each model. Standard Ct cell culture, existing of HeLa cells grown on coverslips, were used as a control to assess growth of Ct strains used for infections of the urethral equivalents. Ct invasion was assessed after 2, 4 and 6 days of incubation. Results: Urethral equivalents consisted of a fully differentiated urethral epithelium on a urethral fibroblast populated collagen hydrogel. The epithelium consisted of multiple differentiated cell layers resembling native urethral tissue. We successfully infected urethral equivalents with a Ct genovar D strain. Ct invasion and expansion was detected in the epithelial layer, but not in the underlying collagen matrix, at 2, 4 and 6 days post infection. Morphological changes of the urethral equivalent could be observed at 2, 4 and 6 days post infection compared to non-infected urethral equivalents, whereby it appeared that the epithelial layer grows around the invaded Ct bacteria. Conclusion: We were able to construct a urethral equivalent resembling native urethral tissue. Moreover, these urethral equivalents could successfully be infected by a Ct genovar D strain, making this a promising life model to investigate the human pathogenesis of urogenital Ct infections.